Mentalizing in psychotherapeutic processes of patients with eating disorders - Zeeck, Almut; Lau, Inga; Endorf, Katharina; Schaefer, Laura; Euler, Sebastian; Lahmann, Claas; Hartmann, Armin (Frontiers in Psychiatry, 2024)
Background: Improvement in the capacity to mentalize (i.e., reflective functioning / RF) is considered both, an outcome variable as well as a possible change mechanism in psychotherapy. We explored variables related to (in-session) RF in patients with an eating disorder (ED) treated in a pilot study on a Mentalization-Based Treatment (MBT) - oriented day hospital program. The research questions were secondary and focused on the psychotherapeutic process: What average RF does the group of patients show in sessions and does it change over the course of a single session? Are differences found between sections in which ED symptomatology is discussed and those in which it is not? Does RF increase after MBT-type interventions? Methods: 1232 interaction segments from 77 therapy sessions of 19 patients with EDs were rated for RF by reliable raters using the In-Session RF Scale. Additionally, content (ED symptomatology yes/no) and certain MBT interventions were coded. Statistical analysis was performed by mixed models. Results: Patients showed a rather low RF, which increased on average over the course of a session. If ED symptomatology was discussed, this was associated with significantly lower RF, while MBT-type interventions led to a significant increase in RF. Conclusions: Results suggest that in-session mentalizing can be stimulated by MBT-typical interventions. RF seems to be more impaired when disorder-specific issues are addressed. Further studies have to show if improving a patient´s ability to mentalize their own symptoms is related to better outcomes.